Analysis Of The Application Of Sharia Principles In Bri Syariah, Bni Syariah, Mandiri And Bank Muamalat - Isa Kholili (International Journal of Economic Research and Financial Accounting, 2023)
The purpose of this study was to analyze the application of the principles of sharia in Islamic Bri syariah, Bni Syariah, Mandiri syariah and Bank Muamalat in running their business unit or units in the aspects of financing and raising funds to customers. Data used in this study is qualitative data and analysis techniques in this research is descriptive qualitative data analysis. The focus of this study, among others, on the application of Islamic principles described by the dimension of capital, raising funds, products and services. Data was collected through several ways including in-depth interviews (depth interview) composed of the heads of units and employees, direct observation (passive participation), and the documents comprising bank Profile, Next, analyze the data using an interactive model. The results of this research is good in all aspects of capital, the fund associations, service to Bri Syariah, Bni Syariah Mandiri and Bank Muamalat basically already implement sharia principles.